TRAINING ON WRITING SCIENTIFIC PAPERS FOR STUDENTS OF SENIOR HIGH SCHOOL 2 TARAKAN - Fathonah, Siti; Selia, Alien Kurnia Warya; Fauziyyah, Nurul Hanna (Abdi Laksana : Jurnal Pengabdian Kepada Masyarakat, 2024)
The purpose of this Community Service activity is to implement one form of Tri Dharma of Higher Education. In addition, this activity aims to be a means of making a major contribution to the development and application of science to the community, which here are students. This training teaches students to understand the systematics and techniques of writing good and correct scientific papers. The method of implementing this activity was carried out using the Participatory Learning and Action (PLA) method. This training activity was conducted offline for 2 days with 50 participants from SMA N 2 Tarakan. The results of community service activities obtained are: 1) the implementation of training in writing scientific papers for high school students N2 Tarakan has been by the stages previously planned, 2) the students' understanding is increasingly mature towards the training material for writing scientific papers, 3) overall the response of the Scientific Writing training participants is very satisfied with the training provided.